A Surgery Issue: Cutting through the Architectural Fabric - Athina Angelopoulou (Footprint)
This essay examines the material ontologies of surgical trans-modifications. Focusing on incisions and subsequent scars, the essay argues for the queering of architecture and design as an act of cutting through structures and processes. I start by rereading a topological body plan, used by surgeons as a guide for performing incisions. I suggest that this plan constitutes a variation within topological representations. It is thus reconceptualised as an internally contradictory representation, calling for dis/continuous cutting acts upon the represented body; that is an amphi-topological representation. The notion of the cut is further approached from the point of view of queer theory and ‘agential realism’. This perspective offers affirmative ways of discussing about acts of cutting. When performed into self-organizing fabrics, cuts appear to act as ‘agents of dis/continuity’. Then, the discussion passes through the genealogy of the architectural section and the building cuts of Gordon Matta Clark, so as to show that the production of buildings by ‘cutting through them to come to matter’ is deep-rooted in the architectural discipline. Next, the philosophical origins of the idea of cutting through the material fabric of the world are sought. It is argued that the latter, beginning as a gnosiological tool, was transformed into a fabricating tool and then into a tool of smoothing the striated. The essay concludes with the presentation of SCARchiCAD; a computational design tool which takes the skin’s wound healing process as a model, offering an interpretation of what the ‘cutting through a virtual form’ could suggest for the design of architectural bodies and the queering of architecture.